A Curriculum in the Post: A Reading of the First Foreign Language Sixth Grade Curriculum through a Posthumanist Lens - Gajauskaitė, Rūta (Acta Paedagogica Vilnensia, 2022)
This paper looks at how the ontological and epistemological premises of posthumanism allow educators to reread a curriculum. Document analysis reveals the current grade 6 first foreign language curriculum in Lithuania as being, in Deleuzian terms, a striated, exhaustive, and positivist one. It is also ridden with tension to meet both the naturally arising learners’ interests and standardized learning outcomes. Posthumanism, which invites educators to look at the curriculum rhizomatically, allows for different kind of learning – defined through thinking, becoming, and affirming.
Keywords: posthumanism; curriculum; becoming; affirming; rhizomatic curriculum